Non-human primates: the appropriate subjects of biomedical research?. Issue 11 (30th October 2007) - Quigley, Muireann
Abstract : Following the publication of the Weatherall report on the use of non-human primates in research, this paper reflects on how to provide appropriate and ethical models for research beneficial to humankind. Two of the main justifications for the use of non-human primates in biomedical research are analysed. These are the "least-harm/greatest-good" argument and the "capacity" argument. This paper argues that these are equally applicable when considering whether humans are appropriate subjects of biomedical research.